Lan Liu: capstone - Liu, Lan, artist and filmmaker (Colorado State University. Libraries, 2019)
The artist's statement: Video is a good medium for people to feel the same feeling more realistically. Therefore, I made some videos to express my understanding of some things through different stages of learning. I chose a vivid color as my main picture tone, and I chose a piece of cheerful music as background music. In this work, I have more focus on the beating melody to let everyone enjoy a cheerful watching. I composed some of my animations through my hand-drawn pictures, as well as graphic design pictures. These videos include my understanding of growth, the meaning of travel, and some purely visual dynamic expressions. We always experience that some people enter our lives and teach us something, but some people will always leave us no matter what they bring us. I am very grateful to the people they have accompanied and the people who have been with them all the time. We also always travel to many different places and take pictures to commemorate our traces. We always return to where we were at the beginning. I put all my understanding of these things in my video.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, images of works and videos.
In motion (After Effects Animation), Dumpling (Animation), and Walking (Animation) videos have no spoken word; A Travel (After Effects Animation) video has no audio.
To request a transcript for Who am I? (Premiere), please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.